Conservative valuation of typical volcanic landscapes in the Pleiku basaltic plateau: some improvement - Tuan, Nguyen Thanh; Chi, Tran Thuy; Khanh, Uong Dinh; Kioko, John Muasya (Vietnam Journal of Earth Sciences, 2020)
There are tens of typical volcano-related relics such as craters and waterfalls in the Pleiku volcanic plateau, Gia Lai province however, Gia Lai’s tourism has underdeveloped. Thus it is vital finding the specific tourist products to promote the provincial nonsmoking industry. Quantifying conservative values of typical volcanic landscapes in the form of money would provide useful information for decision-makers to plan and develop rural tourism. This study was applied to the contingent valuation method to estimate the conservative values of twenty volcanic landscapes in the Pleiku plateau. The results indicated that Bien Ho volcanic landscape got the highest traditional value with above 38.60 billion VND. Subsequently, the conservative value of Chu Dang Ya was 27.28 billion VND. The value of the Phu Cuong waterfall was also estimated quite highly. Furthermore, our new finding is that there was a close relationship between the results coming from the conservative valuation and the results coming from evaluation, classification of geoheritages based on UNESCO’s criteria adapting in Vietnam. The study figured out that there was a close relationship between the conservative valuation and information accessibility on twenty landscapes by interviewees before.